PERLINDUNGAN HUKUM INDIKASI GEOGRAFIS YANG TELAH DIDAFTARKAN SEBAGAI MEREK BERDASARKAN INSTRUMEN HUKUM NASIONAL DAN HUKUM INTERNASIONAL (Lex Jurnalica, 2018)
AbstractThe increasing protection of Geographical Indications in the international is something that is beneficial for Indonesia in order to improve the protection of Intellectual Property Rights, it is because the character of collective or communalistic Geographical Indications ownership is in line with eastern and Indonesian values. The issues raised in this research are how is the Legal Protection of Geographical Indications based on Law Number 20 of 2016 on Trademarks and Geographical Indications and how is the legal protection of Geographical Indications those who have been registered as Trademarks based on National Law Instruments and International Law Instruments. Based on Law Number 20 of 2016 on Trademarks and Geographical Indications, the protection system of Geographical Indications in Indonesia is a constitutive system which requires registration to obtain protection from the State and Geographical Indications cannot be owned individually, but collectively owned by the community who produce Geographical Indication goods. Consequences of the implementation of a first to file system, namely legal protection for Geographical Indications for those who first registered it. The implication of the non-removal of registered brands that have in common with the Geographical Indications by the Minister is that it creates legal uncertainty and injustice. In the event of the use of Geographical Indications as an overseas trademarks, the Lisbon Agreement facilitates the creation of an International registration system for Geographical Indications. Indonesia should be able to benefit from the existence of international instruments that support the protection of Geographical Indications by ratifying the Lisbon Agreement. Keywords: geographical indications, trademarks, intellectual property rights AbstrakMeningkatnya perlindungan Indikasi Geografis di internasional merupakan hal yang menguntungkan bagi Indonesia dalam rangka meningkatkan perlindungan Hak Kekayaan Intelektual,Hal ini karena karakter kepemilikan Indikasi Geografis yang kolektif atau komunalistik sejalan dengan nilai-nilai ketimuran dan keindonesiaan. Permasalahan yang diangkat dalam penelitian ini adalah tentang bagaimanakah Perlindungan Hukum Indikasi Geografis berdasarkan Undang-Undang Nomor 20 Tahun 2016 tentang Merek dan Indikasi Geografis dan mengenai bagaimanakah Pelindungan hukum Indikasi Geografis yang telah didaftarkan sebagai Merek berdasarkan Instrumen Hukum Nasional dan Instrumen Hukum Internasional. Berdasarkan Undang-Undang Nomor 20 Tahun 2016 tentang Merek dan Indikasi Geografis, sistem perlindungan IndikasiGeografis di Indonesia ialah sistem konstitutif yangmensyaratkan adanya pendaftaran untuk mendapatkanperlindungan dari Negara dan Indikasi Geografis tidak dapat dimiliki secara individu, namundimiliki secara kolektif oleh masyarakat penghasil barangIndikasi Geografis. Konsekuensi dari penerapan sistem konsitutif sistem first to file, yaitu perlindungan hukum Indikasi Geografis bagi mereka yang pertama kali mendaftarkannya. Implikasi dari tidak dihapusnya merek terdaftaryang memiliki kesamaan dengan Indikasi Geografis oleh Menteri adalah menimbulkan ketidakpastian hukum dan ketidakadilan. Dalam hal terjadinya penggunaan Indikasi Geografis sebagai merek di luar negeri, Perjanjian Lisabon memfasilitasi dibuatnya sistem registrasi Internasional bagi Indikasi Geografis. Indonesia semestinya dapat mengambil manfaat dengan adanya instrumen internasional yang mendukung perlindungan Indikasi Geografis dengan meratifikasi Perjanjian Lisabon. Kata kunci: indikasi geografis, merek, hak kekayaan intelektual